Volleyball: analysis of attack performed from the backcourt on men’s Brazilian Volleyball Superleague (Brazilian Championship) - Gustavo De Conti Teixeira Costa (Revista Brasileira de Cineantropometria e Desempenho Humano, 2017)
The aim of this study was to identify the effect of attacks from positions 1 and 6 in high-level Brazilian Men’s Volleyball in order to understand the offensive structure of the game. The sample was composed of the observation of 142 2014-2015 Men’s Superleague games, totaling 2969 reception, set and attack actions from positions 1 and 6. The results showed association between place of attack, attack tempo, type of attack and effect of attack (p<0.001). The results showed that the point of attack, when it is performed from position 6, is associated with parallel attack, while, when analyzing position 1, the point of attack is associated with potent diagonal attack. Furthermore, placed attack was associated with game continuity, as well as with low-quality receptions (b and c). In this context, it was concluded the attacking position influences the attack efficacy, according to time and type of attack.